Superlibrarian spreads wings - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
A role model for new-style information professionals, Thiendou Niang has little of the characteristics of the 1970 s generation of librarians from which he came. Timidity, temerity, introversion, a dislike of doing deals, a fear of fixing, none of...